Spectrum of soft tissue sarcomas: Experience of surgery at a tertiary care referral hospital in Central Lahore (Journal of Fatima Jinnah Medical University, 2023)
Background: Soft tissue sarcomas (STS) are malignant tumours arising from mesenchymal tissue, comprising
Keywords: Soft Tissue Sarcoma; Presentation; Resection; Histology; Outcome